Competition and Product Quality in the Supermarket Industry - Matsa, D. A. (Quarterly Journal of Economics, 2011)
This article analyzes the effect of competition on a supermarket firm's incentive to provide product quality. In the supermarket industry, product availability is an important measure of quality. Using U.S. Consumer Price Index microdata to track inventory shortfalls, I find that stores facing more intense competition have fewer shortfalls. Competition from Walmart—the most significant shock to industry market structure in half a century—decreased shortfalls among large chains by about a third. The risk that customers will switch stores appears to provide competitors with a strong incentive to invest in product quality.